Duality of pleasure and pain and its temporal manifestations in Abbasid poetry (Journal of the College of Basic Education, 2023)
Pleasure and pain are among the primary psychological basics of the human self (1) and they are two contradictory principles that govern and control human behavior. Libido" (2) or the instinct of life, which man always seeks to satisfy regardless of all considerations, from seeking pleasure and avoiding pain, and the principle of pain appears in the death instinct (3).It is said that pleasure is ((a kind of liberation or work to get rid of pain)) (4) or it is ((satisfaction of a desire in a way that does not require activity in the sense of vitality. And the feeling of pleasure can be intense, such as achieving a social victory or obtaining more profit ... Or it is the usual sexual pleasure, or eating until full, or the pleasure of satisfying a sadistic impulse, or the intoxication of a drink...)) (5).And if we were to consider the nature of pleasure and pain; To make it clear to us that they are just a symptom or a relationship that accompanies a physical or psychological state: the member who exercises his activity in a correct and usual way, his activity must be associated with a kind of feeling of pleasure, while the member who exercises his activity in a satisfactory and improper way his activity must be accompanied by a feeling With pain, and this matter also affects the psychological aspect (6), bearing in mind that it is not necessary for every pleasure to be good, and every pain to be evil, for some pleasures are evil, such as the pleasure of consuming alcohol, just as some pains may contain something of good, such as the pain arising from a reprimand. The pronoun... (7) Perhaps in his saying I) And perhaps you hate a thing and it is good for you, and perhaps you love a thing and it is bad for you, and God knows best, and you are not good (8).The self is the one who senses that feeling that results from pleasure and pain, and yet it does not dispense with them. In other words, we never feel that we are happy and far from pain until after that happiness in which we were immersed has left us, and perhaps the reason for that is that happiness creates a kind of harmony. between pleasures and the external world, and accordingly, had it not been for pain, we would not feel happiness or pleasure ((There is no creature who did not dream of eradicating all pain in life, so that pleasure alone would prevail in the world, but this beautiful dream is, in fact, a kind of impossibility, because whoever is taken away from Himself the ability to suffer, but deprives himself at the same time of the ability to enjoyment)) (9).We see from the foregoing that pleasure and pain ((two states are linked and there is no way to separate them at all, like the two scales, every movement in one of the two scales would necessarily entail the movement of the other scale)) (10).